2021
DOI: 10.3389/fvets.2021.754625
|View full text |Cite
|
Sign up to set email alerts
|

Hemp Seed Cake as a Novel Ingredient for Dog's Diet

Abstract: In the last few years, the popularity of industrial hemp and its products is increased. From a nutritional point of view, hemp and its products are rich in protein, polyunsaturated fatty acids, vitamins, and useful minerals. Nowadays, the European Commission authorizes the use of hempseed and hempseed oil co-products in animal nutrition. This study is aimed to evaluate the use of hempseed cake in dogs' nutrition, comparing the effect of the supplementation of two lipid sources: swine tallow (T-diet) and hempse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…According to our results, the main fatty acids in the HSM were linoleic (54.09−55.42%), α-linolenic (17.31−18.42%), and oleic (12.96−13.93%) acid, followed by palmitic (6.48−7.90%), stearic (3.18−3.86%), and γ-linolenic (2.61−2.76%) acid [ 18 ]. Similar results were obtained for several commercial HSOs from different industrial hemp varieties, with the main fatty acids (α-linoleic, α- and γ-linolenic, and oleic acid) alone representing 80–90% of the total fatty acids [ 24 , 25 , 33 , 42 , 45 , 46 ]. Longer chain fatty acids, i.e., C:20 or higher, were also detected, but their concentration was significantly lower according to our results [ 46 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…According to our results, the main fatty acids in the HSM were linoleic (54.09−55.42%), α-linolenic (17.31−18.42%), and oleic (12.96−13.93%) acid, followed by palmitic (6.48−7.90%), stearic (3.18−3.86%), and γ-linolenic (2.61−2.76%) acid [ 18 ]. Similar results were obtained for several commercial HSOs from different industrial hemp varieties, with the main fatty acids (α-linoleic, α- and γ-linolenic, and oleic acid) alone representing 80–90% of the total fatty acids [ 24 , 25 , 33 , 42 , 45 , 46 ]. Longer chain fatty acids, i.e., C:20 or higher, were also detected, but their concentration was significantly lower according to our results [ 46 ].…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, the European Commission has authorized the use of hempseed and co-products in animal nutrition as well. Indeed, as demonstrated by a recent in vivo study, hempseed cake is useful in dogs’ nutrition as it leads, after 30 days, to a reduction in liver and renal markers and cholesterol, due to the healthier fatty acid profile [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The probiotic bacteria BSH activity has often been related to a lower cholesterol level [ 54 ]. In this regard, in a previous study [ 13 ], the authors reported a reduction in transaminase and cholesterol in dogs fed hemp oil extraction residue as a source of lipids. Otherwise, the HL1 group’s faeces registered the highest Enterobacteria cell numbers.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, hemp seed and hempseed cakes represent fat and protein sources for farm animals [ 10 , 11 , 12 ]. On this matter, the residue of hemp ( Cannabis sativa L.) oil processing could be a valid resource for lipids and essential fatty acids (LA and ALA) in dogs’ diets [ 13 ]. However, despite the authorization by the European Food Safety Authority (EFSA) to use hemp seed and hempseed co-products as ingredients for all animal species [ 14 ], few data have been published in the literature concerning the use of hemp co-products as a source of PUFAs in pet food.…”
Section: Introductionmentioning
confidence: 99%
“…sativa has gained particular interest in the last years for its low content in tetrahydrocannabinol (THCA) (<0.2-0.3%), a chemical compound responsible for some psychoactive effects, which makes this cultivar suitable for legal cultivation in Europe [2]. For its nutritional characteristics this plant has been studied as feasible feed supplement in various animal species [3][4][5]. As a matter of fact, hemp is characterized by a great content in polyunsaturated fatty acids (PUFA) reaching almost the 80% of total fatty acids (FA), manly linoleic (LA) and alpha-linolenic acids (ALA) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%